Foam Rolling as a Recovery Tool Following Eccentric Exercise: Potential Mechanisms Underpinning Changes in Jump Performance - Drinkwater, Eric J.; Latella, Christopher; Wilsmore, Christopher; Bird, Stephen P.; Skein, Melissa (Frontiers in Physiology, 2019)
Purpose: Recovery from exercise-induced muscle damage (EIMD) is paramount in sports performance. Foam rolling (FR) has been suggested to improve acute performance, however, the ability to facilitate recovery from eccentric (ECC) exercise remains unclear. Methods: Eleven males undertook 6×25 ECC knee extensions to induce muscular damage. Immediately, 24, 48 and 72 h post-training countermovement jump (CMJ), maximal voluntary isometric contraction (MVIC), pressure-pain threshold (PPT), knee flexion range of motion (ROM) and mid-thigh circumference (MTC) were assessed. Neurophysiological measures included voluntary activation (VA), peak twitch torque (PTT), time to peak twitch (PTTtime) and rate of twitch torque development (RTD). Participants then spent 15 min FR prior to each time point, or control (CON). Repeated measures analysis of variance (ANOVA) and standardised effect sizes (Hedges’ g) ± 95% confidence intervals (95%CI) were used to compare FR and CON. Results: CMJ was greater for FR compared to CON (P=0.030) at 72 h (8.6%, P=0.004) with moderate effects observed at 48 and 72 h (g=0.54-0.66). PPT was greater with FR (P=0.018) at 48 h only (23.7%, p=0.013), with moderate to large effects noted at all-time points (g=0.55-0.98). No significant differences were reported for MVIC (P=0.777, -5.1 to 4.2%), ROM (P=0.432, 1.6% to 3.5%), VA (P=0.050, 3.6 to 26.2%), PTT (P=0.302, -3.9 to 9.9%), PTTtime (P=0.702, -24.4 to 23.5%), RTD (P=0.864, -16.0 to -1.0%) or MTC (P=0.409, -0.5 to -0.1%) between conditions. Conclusions: FR appears to improve jump performance in the later stages of recovery following ECC exercise. This may be in part due to improved pain tolerance, however, mechanical and neurophysiological are not modulated with FR.